1994
DOI: 10.1046/j.1471-4159.1994.63041303.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Exocytosis and MARCKS Phosphorylation Are Enhanced by a Metabotropic Glutamate Receptor Coupled to a Protein Kinase C Synergistically Activated by Diacylglycerol and Arachidonic Acid

Abstract: 4-Aminopyridine evokes repetitive firing of synaptosomes and exocytosis of glutamate by inhibiting a dendrotoxin-sensitive K+ channel responsible for stabilizing the membrane potential . We have shown previously that activation of protein kinase C (PKC) by high concentrations of phorbol ester (4,ß-phorbol dibutyrate) can increase release by inhibiting a dendrotoxin-insensitive ion channel, whereas the metabotropic glutamate receptor (mGIuR) agonist (1S,3R)-1-aminocyclopentane-1,3-dicarboxylate [(1S,3R)-ACPD] m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 40 publications
1
36
1
Order By: Relevance
“…The activation of group I mGlu receptors has been shown to be facilitatory at nerve terminals, an effect likely to be the result of DAG production and PKC activation (Herrero et al, 1992;Coffey et al, 1994;Lu et al, 1997;Reid et al, 1999;Thomas et al, 2000). In the present study, we found that SIB1893-mediated inhibition of glutamate was reduced from 19.8 Ϯ 1.5 to 3.0 Ϯ 1.8% and 4.7 Ϯ 1.5% in the presence of PDBu and Ro 32-0432, respectively.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The activation of group I mGlu receptors has been shown to be facilitatory at nerve terminals, an effect likely to be the result of DAG production and PKC activation (Herrero et al, 1992;Coffey et al, 1994;Lu et al, 1997;Reid et al, 1999;Thomas et al, 2000). In the present study, we found that SIB1893-mediated inhibition of glutamate was reduced from 19.8 Ϯ 1.5 to 3.0 Ϯ 1.8% and 4.7 Ϯ 1.5% in the presence of PDBu and Ro 32-0432, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…To confirm that an mGluR5/PLC/PKC cascade is being suppressed by SIB1893 in its inhibition of glutamate, we next examined whether the SIB1893-mediated effect was sensitive to PKC inhibition. Control 4AP (3 mM)-evoked release of 19.4 Ϯ 0.5 nmol/mg/4 min was attenuated by the PKC inhibitor Ro 32-0432 (1 M) to 10.8 Ϯ 0.4 nmol/mg/4 min (n ϭ 5; P Ͻ 0.01), reflecting an inhibition of the reported basal PKC activity present in nerve terminals (Coffey et al, 1994). Crucially, however, in the presence of Ro 32-0432, SIB1893 addition had no further effect on 4AP-evoked glutamate release (10.3 Ϯ 0.7 nmol/ Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The synaptosomal plasma membrane can be depolarized with K + producing a clamped depolarisation, which does not, however, mimic physiological conditions (60). A more physiological membrane depolarisation is evoked by the K + channel inhibitor 4-AP (13).…”
Section: Membrane Depolarizationmentioning
confidence: 99%
“…A direct role for PKC in protein secretion per se is supported by its established roles in mediating the secretion of various cargoes, such as glutamate and noradrenaline from neuronal cell lines (32)(33)(34)(35), mucin from colonic tumor cell lines (36), histamine from rat basophilic leukemia mast cells (37), and insulin and glucagon from pancreatic cells (38 -41). Furthermore, PKC has been reported to interact with a number of proteins associated with intracellular transport (e.g.…”
mentioning
confidence: 99%